Habitat heterogeneity explains mosaics of evergreen and deciduous trees at local‐scales in a subtropical evergreen broad‐leaved forest. (29th December 2016) - Fang, Xiaofeng; Shen, Guochun; Yang, Qingsong; Liu, Heming; Ma, Zunping; Deane, David C.; Wang, Xihua
Abstract: Questions: Mosaics of evergreen and deciduous trees that are characteristic of evergreen broad‐leaved forests (EBLF) are thought to arise from habitat heterogeneity, but empirical evidence for this is limited. We test this assertion asking: (1) whether environmental heterogeneity explains the distribution of deciduous and evergreen trees; (2) which are the most important environmental variables; and (3) does their importance change with scale? Location: Tiantong National Forest Park, Ningbo, Zhejiang, China. Methods: We used data from a 20‐ha individual‐mapped EBLF in spatial point‐pattern analyses testing the scale of aggregation within, and segregation between, the two life forms. We used a heterogeneous Poisson process model to remove the effects of environmental heterogeneity, predicting segregation would disappear if the mosaic was due to habitat heterogeneity alone. Finally, we tested the relative importance of theoretically important environmental variables using multivariate regression trees at three spatial scales (10, 20 and 50 m grid cells). Results: We found evergreen and deciduous trees were aggregated at scales below 125 m and 60 m, respectively, and mutually exclusive at scales <120 m. Evidence of any spatial segregation between the life forms was removed at all scales after controlling for environmental heterogeneity. Only soil phosphorus concentrations contributed to spatial patterns at all scales, with values >0.27–0.30 g·kg −1 favouring deciduous species. Conclusions: Our study is consistent with habitat heterogeneity creating the observed mosaics of evergreen and deciduous tree species, but micro‐habitat heterogeneity contributed even at scales <20 m. Soil phosphorus availability appears to be the major environmental variable maintaining these mosaic patterns at hillslope scales in EBLF. Abstract : We sought to explain the mosaic pattern of evergreen and deciduous trees in a 20‐ha individual‐mapped subtropical evergreen broad‐leaved forest through the use of spatial modelling techniques such as pair‐correlation functions and null models. We show that environmental heterogeneity, especially soil phosphorus availability, is the main factor regulating their coexistence at multiple spatial scales over our study extent.